Combustion behaviors of complex incense stick residues: Multivariate Gaussian process-based optimization of thermal, kinetic, thermodynamic, emission, and ash responses. (1st June 2021) - Wen, Shaoting; Zou, Huihuang; Liu, Hui; Huang, Jianli; Evrendilek, Deniz Eren; Yan, Youping; Li, Weixin; Liu, Jingyong
Graphical abstract: Highlights: Combustion, emission and ash responses of incense sticks were quantified. Activation energy of the second and third stages was 157.4 and 251.7 kJ/mol. Their reaction mechanisms were best described by D3 and R2 models. NH3 and SO2 showed similar release pattern with only one peak at 320 °C. Efficiency and emission were optimized using multivariate Gaussian process models. Abstract: In order for second-generation feedstocks to be fed back to circular economies, both economic and environmental benefits of the thermochemical conversion need to be maximized in the context of the cradle-to-grave/cradle waste management. This study aimed to quantify and optimize the combustion performance and flue gas emissions of incense sticks (IS). The IS combustion consisted of three stages, with a main weight loss of 69.6% between 185 and 477 °C at 10 °C/min. Mean activation energy was estimated at 157.4 and 251.7 kJ/mol for the main second and third reaction stages. CO2 and H2 O were the main evolved gases, while NH3 and SO2 exhibited a similar release pattern by peaking at 320 °C. Multivariate Gaussian process model-based optimizations pointed to 525 °C as the optimal setting for both three combustion responses and the emission reduction of nine flue gases. A 63% rise in the combustion temperature from 322 to 525 °C on average reduced the emissions by 79%.